Understanding mobility on campus using Wi-Fi localisation - Ting, Grace Yan Teng (2019)
The education service is progressing along with the advancement in technology. Staying connected is paramount to any institution, and as a result, massive amounts of data from network connections have been generated in the process. This project therefore aims to provide greater insights about library usage by testing the hypothesis – the usage of libraries is shifting away from being a source of reference materials/books, to becoming a quiet place for studying. This is achieved by processing the network connection data, obtained from the National University of Singapore, by writing a Python script. The process data is then stored into a MySQL database, visualised on a front-end web application written in ReactJS, and analysed by writing a R script. Furthermore, the project conducts an exploratory analysis on the data specific to the Central Library. Some notable findings include: a 350% increase in users on level 3 (which contains the quiet area and carrels) than on level 6, and 77% of users are students. Although the results from the quantitative analysis, on Academic Year 2017/2018 Semester 2, using Welch’s t-test failed to conclude that the library usage is shifting primarily to a place for studying. However, the data does however conclude with a 95% confidence interval, that the normal term has more users than the examination period. With these findings, this project looks to propose the following recommendations which will be covered below with regards to the space utilisation, university’s devices, and informational posters.